Efficacy of Schema Therapy training on self-efficacy, self-esteem and assertiveness in women heads of households covered by welfare in Karaj - Moradi, Shiva; Moradi, Shahrzad (Psychology of Woman Journal, 2023)
Present study was conducted to investigate the effectiveness of schema therapy training on self-esteem, self-efficacy and courage of female-headed households. The research design was pretest-posttest with the control group. The statistical population included all female-headed households covered by Karaj Welfare in 1400. Targeted sampling was performed on all eligible individuals from the statistical population. In addition to completing the Rosenberg Self-Esteem Questionnaire(1965) , Scherer et al. Self-efficacy questionnaires(1982), and Gambrill and Rigi (1975), audacity questionnaires, 40 individuals with the lowest scores in each component were randomly assigned to experimental and control groups (20 in each group). The experimental group was then trained in a ten-session schema therapy protocol. Finally, post-test was performed for both groups. Then, the data were analyzed by analysis of covariance in SPSS software version 26. The results of data analysis showed that group training in schema therapy is effective on increasing self-efficacy, self-esteem and courage in female-headed households (p